1999
DOI: 10.1080/07448489909595644
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Academic Functioning in College Students With Attention Deficit Hyperactivity Disorder

Abstract: Attention deficit hyperactivity disorder (ADHD) has been increasingly recognized as a valid adult diagnosis. Yet the impairments related to ADHD in college students have received little scholarly attention. Psychological and academic impairments in college students not previously diagnosed with ADHD were assessed in a retrospective chart review, using specifically defined diagnostic criteria, and compared with a control group. Students with ADHD had a significantly lower mean grade point average, were more lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
165
1
10

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(188 citation statements)
references
References 17 publications
12
165
1
10
Order By: Relevance
“…Although ADHD must first manifest in childhood to warrant diagnosis, numerous longitudinal research studies have shown that the symptoms of this disorder rmay continue into adulthood (Barkley, 1998;Shekim, Asarnow, Hess, Zaucha, & Wheeler, 1990). ADHD affects 2% and 11% of the college student population (DuPaul, Weyandt, O'Dell, & Varejao, 2009;Weyandt & DuPaul, 2008), and college students who are diagnosed with ADHD are at increased risk of being placed on academic probation, having a lower grade point average, experiencing more academic problems, and failing repeatedly than are students without this disorder (Blasé et al, 2009;Heiligenstein, Guenther, Levy, Savino, & Fulwiler, 1999;Norvilitis, Sun, & Zhang, 2010;Norwalk, Norvilitis, & MacLean, 2009). Despite these potential academic difficulties, young adults with ADHD are enrolling in postsecondary education in increasing numbers (Dipeolu, 2011;DuPaul et al, 2009;Weyandt & DuPaul, 2008), and all higher education institutions are mandated by federal law (Section 504 of the Rehabilitation Act, 1977) to provide services and accommodations to ensure success in the academic and career pursuits of these students.…”
mentioning
confidence: 99%
“…Although ADHD must first manifest in childhood to warrant diagnosis, numerous longitudinal research studies have shown that the symptoms of this disorder rmay continue into adulthood (Barkley, 1998;Shekim, Asarnow, Hess, Zaucha, & Wheeler, 1990). ADHD affects 2% and 11% of the college student population (DuPaul, Weyandt, O'Dell, & Varejao, 2009;Weyandt & DuPaul, 2008), and college students who are diagnosed with ADHD are at increased risk of being placed on academic probation, having a lower grade point average, experiencing more academic problems, and failing repeatedly than are students without this disorder (Blasé et al, 2009;Heiligenstein, Guenther, Levy, Savino, & Fulwiler, 1999;Norvilitis, Sun, & Zhang, 2010;Norwalk, Norvilitis, & MacLean, 2009). Despite these potential academic difficulties, young adults with ADHD are enrolling in postsecondary education in increasing numbers (Dipeolu, 2011;DuPaul et al, 2009;Weyandt & DuPaul, 2008), and all higher education institutions are mandated by federal law (Section 504 of the Rehabilitation Act, 1977) to provide services and accommodations to ensure success in the academic and career pursuits of these students.…”
mentioning
confidence: 99%
“…This suggests that exposure to cocaine and other drugs of its class may have a greater potential for enhancing the addiction process among adolescents than among adults, both of which are growing populations exposed to MP (Shaffer 1994;Robin 1999). Given that the use of therapeutic stimulants has become extended (Heiligenstein et al 1999) and that adolescents may be more sensitive to aspects of the drug that make it more reinforcing, our animal model was appropriate for studies on the effects of adolescent MP exposure. …”
mentioning
confidence: 99%
“…A2008 study, however, foundno more use of drugs and alcohol among those with ADHD than those without (Rabinereta.l, 2008). A much earlier study, in 1999,also found no difference in depression, anxiety, interpersonal relationships or substance use between those with and without ADHD (Heiligenstein et al, 1999).…”
Section: Knight Knight and Killionmentioning
confidence: 86%
“…These behaviors interfere with classroom control and lead to poor academic performance for all students. Between 5 and 10% of children in the United States have been diagnosed with ADHD (Vance & Weyandt, 2008;Heiligenstein et al, 1999).Interestingly, African American and Hispanic children are diagnosed with ADHD at only half the rate of Caucasian children (Rothe, 2005) and Non-Hispanic white males have the highest rate of diagnosis (Vance &Weyandt, 2008). Though it used to be believed that children "outgrew" this disorder, it has now become more accepted among diagnosticians that this disorder continues into adulthood even though ADHD symptoms decrease with age by approximately 50% every five years (Heiligenstein, Conyers, Berns, & Smith, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation